Interaction Between NOS3 and HMOX1 on Antihypertensive Drug Responsiveness in Preeclampsia - Sandrim, Valeria Cristina [UNESP]; Luizon, Marcelo Rizzatti; Pilan, Eliane [UNESP]; Caldeira-Dias, Mayara [UNESP]; Coeli-Lacchini, Fernanda Borchers; Kors, Georgia [UNESP]; Berndt, Iuly [UNESP]; Lacchini, Riccardo; Cavalli, Ricardo Carvalho (Federacao Brasileira Soc Ginecologia & Obstetricia-febrasgo, 2020)
Objective We examined the interaction of polymorphisms in the genes heme oxygenase-1 (HMOX1) and nitric oxide synthase (NOS3) in patients with preeclampsia (PE) as well as the responsiveness to methyldopa and to total antihypertensive therapy. Methods The genes HMOX1 (rs2071746, A/T) and NOS3 (rs1799983, G/T) were genotyped using TaqMan allele discrimination assays (Applied Biosystems, Foster City, CA, USA), and the levels of enzyme heme oxygenase-1 (HO-1) were measured using enzyme-linked immunosorbent assay (ELISA). Results We found interactions between genotypes of the HMOX-1 and NOS3 genes and responsiveness tomethyldopa and that PE genotyped as AT presents lower levels of protein HO-1 compared with AA. Conclusion We found interactions between the HMOX-1 and NOS3 genes and responsiveness to methyldopa and that the HMOX1 polymorphism affects the levels of enzyme HO-1 in responsiveness to methyldopa and to total antihypertensive therapy. These data suggest impact of the combination of these two polymorphisms on antihypertensive responsiveness in PE.
Keywords: preeclampsia; polymorphism; antioxidant; nitric oxide